The methodological path of research in the prison environment in the area of information science: Limits and potentialities of the ethnography - Monteiro, Ciro Athayde Barros [UNESP] (Universidade Federal da Paraíba, 2020)
Ethnography is an essential methodological approach to understand the social demands of the field of Information Science and can be used in different environments, among them, in prison. The aim of this article is to expose the methodological path that I followed inside the prison when conducting field research for the development of the thesis Incarcerated information: The young man of the 'internet generation' and the mediation and appropriation of informational devices inside the prison using ethnography as a qualitative research methodology within the scope of Information Science (CI). In this article, I present some concepts and reflections about the potential and limits of this methodology and report the paths I took to collect the data, detailing how the universe was chosen, the application of the research instruments, the questions that arose throughout the study, the selection of the participants, and the challenges to carry out the research. The description of the methodological path presents the reader with the possibilities of using ethnography, both in prison and in other environments that arouse the interest of the area. In the specific case of prison, the use of ethnography was quite significant, proving to be flexible, with mechanisms for registering and apprehending subjectivities, capable of making an interpretive dive into the universe of research. In addition, this methodology provides a constant renewal of view regarding the area's episteme and its forms of social action.
O percurso metodológico de uma pesquisa no ambiente prisional na área de ciência da informação: Limites e potencialidades da etnografia
Keywords: Devices and Information Science; Ethnography; Methodology; Prison Library